Materials containing ion transport interfaces, preparation methods, and applications thereof

By chemically bonding an amorphous interfacial layer to silicon electrodes using metal chlorides and lithium sulfides, the ion transport interface addresses issues of low conductivity and compatibility, enhancing battery performance and stability in solid-state batteries.

JP7621448B2Active Publication Date: 2025-01-24CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023196171
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-29
Filing Date
2023-11-17
Publication Date
2025-01-24
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

Silicon negative electrodes in solid-state batteries face issues with low lithium ion diffusion coefficient, volumetric expansion, and poor chemical compatibility with sulfide electrolytes, leading to reduced performance and increased risk of redox reactions and dendrite formation.

Method used

A material with an ion transport interface is created by chemically bonding an amorphous interfacial layer to silicon or silicon alloy surfaces through epitaxial growth deposition, using a chemical reaction with metal chlorides and lithium sulfides to form a protective layer with high ionic conductivity and stability.

Benefits of technology

The ion transport interface enhances lithium ion conductivity and stability, improving the performance and cycle stability of silicon-based negative electrodes in solid-state batteries, while preventing side reactions and dendrite formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621448000001
    Figure 0007621448000001
  • Figure 0007621448000002
    Figure 0007621448000002
  • Figure 0007621448000003
    Figure 0007621448000003
Patent Text Reader

Abstract

To provide a material including an ion-transporting interface when using silicon and its alloy as an anode material of a solid-state battery, a preparation method, and its application.SOLUTION: A material comprises silicon and / or a silicon alloy material, and a surface of the material has an amorphous interface layer including LixMSy having an ion conduction performance.EFFECT: A protective layer obtained by this invention has not only high ionic conductivity but also advantages such as high stability to an electrolyte material such as sulfides and stability to air, thus, incompatibility between silicon and its alloy anode material with sulfide electrolyte materials can be mitigated effectively, and a multiplier performance and a cycle stability of silicon and its alloy anode in use processes of a solid-state battery can be improved effectively.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of battery technology, in particular to a material containing an ion transport interface, a preparation method and its application. [Background technology]

[0002] Solid-state batteries are expected to achieve higher safety and higher energy density through the use of non-flammable solid electrolyte materials and compatibility with many anode and cathode materials with high energy density. To increase the energy density of solid-state batteries, the activity and capacity of the anode material play an important role. Among them, common solid electrolyte materials such as sulfide solid electrolytes have a narrower electrochemical window, which makes them more susceptible to oxidation-reduction reactions, and they have a large interfacial impedance with the anode material during the testing process of solid-state batteries, which makes them more susceptible to lithium dendrites and short-circuiting the battery. Therefore, constructing a stable interface between the solid-state battery electrolyte and the anode is the key to realizing high-performance all-solid-state batteries.

[0003] Silicon is one of the excellent anode materials, but silicon anodes have the following problems:

[0004] 1. The diffusion coefficient of lithium ions is low, which is unfavorable to the effective transport of lithium ions during the charging and discharging process of the battery.

[0005] 2. When lithium is embedded in the silicon anode, it causes a huge volume expansion, which reduces the performance of the battery.

[0006] 3. The chemical compatibility between silicon and its lithiation products and sulfide electrolyte materials is poor, and side reactions are likely to occur at the interface, which further limits the ion / electron conduction process of silicon active materials. Summary of the Invention [Problem to be solved by the invention]

[0007] When silicon and its alloys are used as negative electrode materials in solid-state batteries, they suffer from the problems of lower ionic conductivity and lower stability to sulfide electrolyte materials. The present invention provides a material containing an ion transport interface, a preparation method and its application to solve the above problems. [Means for solving the problem]

[0008] The present invention is realized by the following technical solutions:

[0009] A material comprising an ion transport interface, the material being a silicon and / or silicon alloy material, the surface of the material having ion conduction capability, Li x MS y where 0≦x≦6, 0≦y≦4, and both x and y are integers; and M=one or more of Si, Sn, Ge, Al, Ga, In, Zn, Cu, Ti, Cr, Fe, Co, Ni, and Mn.

[0010] Further optionally, the Li x MS y The contact between the amorphous interfacial layer, including the silicon and / or silicon alloy material, is by chemical bonding, epitaxial growth deposition interaction, rather than physical contact.

[0011] More preferably, the silicon alloy material is SiM' k where M'=one or more of Al, Cr, Mn, Cu, Zn, Ca, Mg, Sn, C, Fe, Co, Ni, and Ti, and 0≦k≦3.

[0012] A method for preparing the above-mentioned ion transport interface-containing material, comprising chemically reacting a surface of a silicon and / or silicon alloy material using in-situ synthesis to form an interface layer.

[0013] Due to the effect of the in situ reaction, the obtained composite material does not show any obvious sulfide particles or agglomerates. xMS y The amorphous interfacial layer, comprising Li, reacts with silicon and / or silicon alloy materials by in situ chemical reaction to form epitaxial deposits on the surface thereof. x MS y The contact between the amorphous interfacial layer, including the silicon and / or silicon alloy material, is by chemical bonding, epitaxial growth deposition interaction, rather than physical contact.

[0014] More selectively, The present invention relates to a method for producing a chlorine-rich structure on a surface of a silicon and / or silicon alloy material by chemically reacting the surface of the material with a solution containing at least one metal chloride, and then subjecting the chlorine-rich structure on the surface of the material to a vulcanization reaction to deposit a nanoscale vulcanization product on the surface in situ, thereby producing a Li ion-conducting material having ion-conducting ability. x MS y and forming an amorphous interface layer comprising:

[0015] Further alternatively, the raw material used in the vulcanization reaction is Li2S a where 1≦a≦8.

[0016] More selectively, At least one MCl x and adding silicon and / or silicon alloy materials and allowing to react; Li2S a and continuing the reaction by adding an organic solution containing: After the reaction is completed, a drying process is performed to obtain a material including an ion transport interface.

[0017] More optionally, the MCl x , silicon and / or silicon alloy materials, Li2S a The amount of each of the additives is adjusted in a mass ratio of n:m:l, where 0.1≦n≦10, 90≦m≦99.5, and 0.2≦l≦15.

[0018] More optionally, the MCl xThe organic solvent employed in the organic solution may include one or more of esters, ethers, amides, ketones, CS2 solvents, and tetrahydrofuran solvents, and / or Li2S a The organic solvent employed in the organic solution includes one or more of esters, ethers, amides, ketones, CS2 solvents, and tetrahydrofuran solvents.

[0019] More preferably, the drying temperature of the drying treatment is 60°C to 150°C.

[0020] The application of the material comprising an ion transport interface in a solid-state battery, wherein the material is the material comprising an ion transport interface described above, or is prepared by the method for preparing the material comprising an ion transport interface described above.

[0021] More optionally, it is used as an anode material in a solid-state battery.

[0022] The material including the ion transport interface provided by the present invention finds application in all-solid-state batteries and is used as an anode material in solid-state batteries, more preferably in lithium batteries.

[0023] A lithium (ion) battery, a silicon and its alloy composite material comprising the rapid ion transport interface; A positive electrode and A negative electrode; and an electrolyte interposed between the positive electrode and the negative electrode, the electrolyte including a sulfide solid electrolyte, an oxide solid electrolyte, a halide electrolyte, a nitride electrolyte, a polymer electrolyte, an organic electrolyte, or a combination thereof. Effect of the Invention

[0024] The present invention has the following advantages and beneficial effects:

[0025] 1. The material containing an ion transport interface provided by the present invention is capable of transporting Li on the surface of silicon and silicon alloy particles. x MS yThe resulting protective layer not only has high ionic conductivity, but also has the advantages of high stability against electrolyte materials such as sulfides and stability against air. It can effectively alleviate the incompatibility between silicon and its alloy anode materials and sulfide electrolyte materials, and can effectively improve the multiplication performance and cycle stability of silicon and its alloy anodes during the use of solid-state batteries.

[0026] 2. The material containing the ion transport interface provided by the present invention adopts in situ epitaxial deposition, so that silicon and silicon alloy particles and Li x MS y Since the interface layer is rich in ZnO and has chemical bonds that interact with each other, the contact between the particles is closer than the physical contact between the particles, and the interface ion conduction effect is better.

[0027] 3. The preparation method of the material containing ion transport interface provided by the present invention has a simple preparation method, abundant raw materials, low cost, easy to use, and easy to scale up. At the same time, the obtained material has good performance and can effectively inherit the advantages of silicon anode materials in solid-state batteries, which contributes to the development of high energy density solid-state batteries. [Brief description of the drawings]

[0028] The drawings described herein form a part of this application and are included to provide a further understanding of the embodiments of the present invention and are not to be construed as limitations thereon. [Figure 1] FIG. 1B and FIG. 1C are scanning electron microscope images and energy spectra of the silicon micron material with abundant Li4SiS4 interfacial layer on the surface prepared in Example 1; FIG. 1B and FIG. 1C are scanning electron microscope images under different magnification conditions, and FIG. 1D is the scanning electron microscope energy spectrum. [Diagram 2]FIG. 2 is a comparison diagram of charge / discharge curves of the lithium-silicon solid battery assembled in Example 1 and Comparative Example 1. FIG. 2(a) is a charge / discharge curve of the lithium-silicon solid battery assembled in Comparative Example 1, and FIG. 2(b) is a charge / discharge curve of the lithium-silicon solid battery assembled in Example 1. [Diagram 3] 3 is a comparison diagram of the cycle stability of the lithium-silicon solid battery assembled in Example 1 and Comparative Example 1. In Fig. 3, the curve with symbol □■ is the cycle stability curve of the lithium-silicon solid battery assembled in Example 1, and symbol ▼ is the Coulombic efficiency curve of the lithium-silicon solid battery assembled in Example 1. In Fig. 3, the curve with symbol ○● is the cycle stability of the lithium-silicon solid battery assembled in Comparative Example 1, and symbol ▲ is the Coulombic efficiency curve of the lithium-silicon solid battery assembled in Comparative Example 1. [Figure 4] The chemical reaction calculation diagram of silicon and silicon lithiation products and sulfide electrolyte material, and the chemical reaction calculation diagram of silicon micron material with abundant Li4SiS4 protective layer on the surface and sulfide electrolyte material, Figure 4a is the chemical reaction energy curve of Si and Li3PS4 electrolyte material, Figure 4b is the chemical reaction energy curve of Li22Si5 and Li3PS4 electrolyte material, Figure 4c is the chemical reaction energy curve of Li4SiS4 and Li3PS4 electrolyte material, and Figure 4d is the chemical reaction energy curve of SiS2 and Li3PS4 electrolyte material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] In order to make the objectives, technical solutions and advantages of the present invention clearer and easier to understand, the present invention will be described in more detail below in conjunction with the examples and drawings, but the outline embodiments of the present invention and their description are only used for the purpose of interpreting the present invention and are not intended to limit the present invention.

[0030] Example 1 This embodiment provides a material that includes an ion-transport interface, i.e., a silicon micron material that is enriched with a Li4SiS4 interface layer on its surface.

[0031] 1. Preparation of silicon micron materials with abundant Li4SiS4 interfacial layer on the surface In an argon-filled glove box, 17 mg of silicon tetrachloride was weighed out and dissolved in 100 ml of tetrahydrofuran solution, and after leaving it for 30 minutes, it was recorded as a tetrahydrofuran solution of silicon tetrachloride and was left on standby. In addition, 9.2 mg of lithium sulfide and 12.8 mg of monosulfur powder were weighed out and dissolved in 100 ml of tetrahydrofuran solution with stirring to obtain a clear solution, which was left on standby for 30 minutes and recorded as a tetrahydrofuran solution of Li2S4 and was left on standby.

[0032] In a glove box, 150 mg of micron silicon particles were weighed into a glass bottle, 10 ml of the above-constituted silicon tetrachloride tetrahydrofuran solution was added, and the mixture was stirred for 1 hour using a magnetic stirrer. Then, during the stirring process, 10 ml of the above-constituted Li2S4 tetrahydrofuran solution was added slowly, the whole process was continued for 30 minutes, and after the addition was completed, the stirring was continued for 1 hour. The resulting reaction solution was transferred to a vacuum drying box and vacuum dried at a drying temperature of 80°C and a drying time of 12 hours. The obtained material is a silicon micron material with an abundant Li4SiS4 protective layer on the surface.

[0033] 2. Preparation of silicon anode material for solid-state batteries In a glove box, 60 mg of silicon micron material with a rich Li4SiS4 interface layer on the surface, 30 mg of Li3PS4 sulfide solid electrolyte material, and 10 mg of graphite powder were weighed, polished in a mortar for 30 minutes, and then allowed to stand.

[0034] 150 mg of Li3PS4 sulfide solid electrolyte material was weighed, placed in a mold cell liner, and then pressed at a pressure of 150 MPa to produce an electrolyte sheet. Then, one end of the electrolyte sheet was coated with Li x SiS yThe silicon micron material rich in interfacial layer was added and paved, and then pressed under a pressure of 350 MPa. Then, an unmodified lithium wafer was added to the other end of the electrolyte sheet, and pressed under a pressure of 50 MPa to assemble the lithium-silicon solid-state battery. The test used constant current charging and discharging, with a current of 0.1 mA cm. -2 The voltage range was 0.005 to 2.0 V.

[0035] Example 2 The present embodiment provides a material containing an ion transport interface, i.e., a silicon alloy micron material with a surface enriched Li3AlS3 interfacial layer.

[0036] 1. Preparation of silicon alloy micron material with abundant Li3AlS3 interfacial layer on the surface The preparation method is the same as that shown in Example 1, except that the 1 mmol / L SiCl4 tetrahydrofuran solution was replaced with 1 mmol / L AlCl3 tetrahydrofuran solution. Specifically, 13.3 mg of aluminum trichloride was weighed out, dissolved in 100 ml of tetrahydrofuran solution, and left for 30 minutes, after which it was recorded as a tetrahydrofuran solution of aluminum trichloride and allowed to stand, and the micron silicon particles were dissolved in SiFe 0.2 It was replaced by micron particles of alloy.

[0037] 2. Preparation of silicon anode material for solid-state batteries The preparation method is as shown in Example 1, except that the sulfide solid electrolyte material is a commercially available Li6PS5Cl electrolyte material.

[0038] Example 3 This example is directed to a material that includes an ion transport interface, i.e., Li x Al 0.2 S 0.8 S y To provide a silicon micron material rich in an interfacial layer.

[0039] 1. Li on the surface x Al 0.2 S 0.8 S yPreparation of silicon micron materials rich in interfacial layers. The preparation method is the same as in Example 1, except that the 1 mmol / L SiCl4 tetrahydrofuran solution was replaced with a SiCl4 and AlCl3 tetrahydrofuran solution, and the molar ratio of SiCl4 to AlCl3 was 4:1. Specifically, 2.66 mg of aluminum trichloride and 13.6 mg of silicon tetrachloride were weighed out and dissolved in 100 ml of tetrahydrofuran solution, and the solution was left for 30 minutes, after which it was recorded as a tetrahydrofuran mixed solution of SiCl4 and AlCl3 and was left on standby. The micron silicon particles were mixed with SiAl 0.2 Switched to alloy micron particles.

[0040] 2. Preparation of silicon anode material for solid-state batteries The preparation method was the same as in Example 1, except that three layers of a commercially available Li6PS5Cl electrolyte material and a ball mill-synthesized Li2ZrCl6 electrolyte material were used as solid electrolyte materials, with the Li2ZrCl6 electrolyte material placed in the middle layer and the Li6PS5Cl electrolyte material placed on both ends.

[0041] Comparative Example 1

[0042] The micron silicon particles used in Example 1 were used directly, but the micron silicon particles were not subjected to an in-situ reaction process, and no interfacial layer with rapid ion transport was formed on the surface of the silicon particles.

[0043] As a comparative example, the process of preparing the silicon negative electrode material solid-state battery is the same as that of Example 1, except that the micron silicon particles used are not subjected to the process of in-situ reaction, and no interfacial layer with rapid ion transport is formed on the surface of the silicon particles.

[0044] Comparative Example 2 A comparative analysis was performed using theoretical calculations, and Si, Li 22 The chemical reaction energy between each of the electrolyte materials, Si5, Li4SiS4, SiS2, and Li3PS4, was calculated, and the interface between the electrolyte material and the silicon anode material was qualitatively evaluated based on the chemical reaction energy.

[0045] Performance Testing 1, Test method: (1) Scanning Electron Microscope: The scanning electron microscope test was performed using a field emission scanning electron microscope S4800 manufactured by Hitachi, Ltd. of Japan. The specific steps were as follows: 1) prepare the sample in a glove box, attach a conductive adhesive to the sample stage, and then sprinkle the sample powder directly onto the conductive adhesive to adhere it; 2) use a vacuum sample transfer stage to directly transfer the sample to the vacuum chamber of the scanning electron microscope for vacuum treatment; 3) adjust the shooting mode and energy spectrum mode of the scanning electron microscope to take images.

[0046] (2) Electrochemical performance test method: The silicon anode material solid-state battery test was performed by constant current charging and discharging, and the entire test process was performed at a set current of 0.1 mA cm -2 The test was performed using a blue electromechanical electrochemical tester with a voltage range of 0.005 to 2.0 V.

[0047] 2. Test results: FIG. 1 is a scanning electron microscope image and energy spectrum of the silicon micron material prepared in Example 1, the surface of which is rich in Li4SiS4 interfacial layer, and no obvious sulfide particles or aggregates are found in the figure.

[0048] FIG. 2a shows the charge / discharge curve of the lithium-silicon solid-state battery assembled in the comparative example, and FIG. 2b shows the charge / discharge curve of the lithium-silicon solid-state battery assembled in the comparative example.

[0049] In FIG. 3, the curve marked with the symbol □■ is the cycle stability curve of the lithium-silicon solid-state battery assembled in Example 1, and the curve marked with the symbol ▼ is the Coulomb efficiency curve of the lithium-silicon solid-state battery assembled in Example 1.

[0050] In FIG. 3, the curve marked with the symbols ○● is the cycle stability of the lithium-silicon solid-state battery assembled in Comparative Example 1, and the curve marked with the symbol ▲ is the Coulombic efficiency curve of the lithium-silicon solid-state battery assembled in Comparative Example 1.

[0051] FIG. 4 shows the structure of silicon and the silicon lithiation product Li 22 Chemical reaction diagram of Si5 and sulfide electrolyte material, and Li on the surface x SiS y 1 is a diagram showing the chemical reaction between a silicon micron material and a sulfide electrolyte material rich in an interfacial layer.

[0052] Detailed comparison between Example 1 and Comparative Example 1 shows that the silicon micron material with Li4SiS4 interfacial layer on the surface has higher cycle stability and lower electrode polarization curve, which indicates that the silicon micron material with Li4SiS4 interfacial layer on the surface has higher electrochemical stability during solid-state battery cycle.

[0053] Theoretical calculations show that silicon and the silicon lithiation product Li 22 It shows that the spontaneous reaction energy between Si5 and sulfide electrolyte material is more, exceeding 0.14eV / atom. In comparison, the main components of the interface layer on the surface of silicon micron material with abundant Li4SiS4 interface layer on the surface are Li4SiS4 and SiS2, and both of them and Li3PS4 electrolyte material show reaction energy less than 0.008eV / atom, indicating that Li4SiS4 and SiS2 have no obvious chemical reaction with Li3PS4 electrolyte material, and can effectively block the side reaction between silicon anode material and sulfide electrolyte material.

[0054] The above-mentioned specific embodiments further explain the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. 1. A method for preparing a material comprising an ion transport interface, comprising: the material is silicon and / or a silicon alloy material; The surface of the material has ion conducting capability, Li x MS y and an amorphous interface layer comprising: 0<x≦6, 0<y≦4, M=at least one of Si and Al; The method of preparing the material comprising an ion transport interface comprises chemically reacting a surface of a silicon and / or silicon alloy material to form an interface layer using an in situ synthesis method, and chemically reacting a surface of the silicon and / or silicon alloy material to form a chlorine-containing structure at the surface by immersing the surface of the silicon and / or silicon alloy material in a solution comprising at least one metal chloride; Then, the chlorine-containing composition on the surface of the material is subjected to a vulcanization reaction to deposit a vulcanization product having an average particle size of nanoscale size on the surface in situ, thereby forming a Li x MS y forming an amorphous interface layer comprising A preparation method comprising the steps of:

2. The Li x MS y The amorphous interfacial layer, including the silicon and / or silicon alloy material, is in contact with each other by the action of chemical bonding, epitaxial growth deposition.

2. The method according to claim 1 .

3. The silicon and / or silicon alloy material is SiM' k M' is one or more of Al, Cr, Mn, Cu, Zn, Ca, Mg, Sn, C, Fe, Co, Ni, and Ti, and 0<k≦3.

2. The method according to claim 1 .

4. The raw material used in the vulcanization reaction is Li 2 S a and 1≦a≦8.

2. The method according to claim 1 .

5. At least one MCl x and reacting the organic solution containing the above-mentioned compound by adding silicon and / or silicon alloy material. Li 2 S a and continuing the reaction by further adding an organic solution containing (wherein 1≦a≦8); After the reaction is completed, a drying process is performed to obtain a material including an ion transport interface.

5. The method according to claim 4 .

6. The MCl x , silicon and / or silicon alloy materials, Li 2 S a The amounts of the additives are adjusted in a mass ratio of n:m:l, where 0.1≦n≦10, 90≦m≦99.5, and 0.2≦l≦15.

6. The method according to claim 5 .

7. The MCl x The organic solvents used in the organic solution are esters, ethers, amides, ketones, CS 2 and / or one or more of Li 2 S a The organic solvents used in the organic solution are esters, ethers, amides, ketones, CS 2 solvent, and tetrahydrofuran solvent.

7. The method according to claim 6 .

8. A method for producing a solid-state battery, comprising using a material obtained by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • All-solid lithium ion secondary battery

    JP2018073513A

  • All-solid battery and manufacturing method thereof

    JP2019197728A

  • Negative-electrode material and lithium secondary battery using same

    WO2010131709A1

  • Silicon-carbon composite material for secondary lithium battery and preparation method therefor

    WO2021254142A1